(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Surfactants form a unique class of chemical compounds. This review provides an introduction to the nature and physical properties of surfactants, emphasizing their ability to radically alter surface and interfacial properties and to self-associate and solubilize themselves in micelles. These properties provide the means to apply surfactants in wettability modification, detergency, and the displacement of liquid phases through porous media on one hand, and to stabilize dispersions (including foams, froths and emulsions), or to destabilize dispersions (again including foams and emulsions) on the other hand. These in turn lead to a vast array of practical application areas which are illustrated in terms of mineral and petroleum processing, biological systems, health and personal care products, foods, and crop protection.